Knowledge Sharing in an Electronics Manufacturing Firm: Evidence from Malaysia - Mohammed, Nurliza Fathi; Uchenna C, Eze; Gerald Goh Guan, Gan (2009)
The objective of this paper is to determine the knowledge sharing behavioral intentions among employees. We developed nine hypotheses on the behavioral intentions of employees with respect to sharing knowledge, which are grounded on theory. In addition, we used 141 valid survey responses from an electronics manufacturing firm in Malaysia and analyzed the data using correlation and regression statistical techniques. The findings in this paper could help provide some materials that managers could use to improve knowledge sharing capacity in a manufacturing firm, which may be useful in related areas such as product life cycle, new product development and customer services. Managers could also use the results to seek for avenues to encourage knowledge sharing among employees in the firm. This paper contributes to the existing body of literature on knowledge sharing. The findings and explanation for the hypotheses are discussed including the implications for research, practice and suggestion for future research.